CLINICAL STUDY OF BABOOL (ACACIA ARABICA WILLD.) AND KUKUNDAR (BLUMEA LACERA D.C.) ON ASRIGDARA (AYUSHDHARA, 2019)
Rakta is known to be a vital substance of body. As the disease is characterized by excess flow of blood out of the body, Raktastambhana Chikitisa is beneficial. Treatment prescribed for Raktatisara, Raktapitta, Raktarsha, Guhyaroga and Garbhasrava is also useful. Considering this aspect, Raktastambhaka, Raktsodhana, Raktapittaghna effects are desired in treatment. Haemostatic drugs should be used by giving due consideration to the association of Doshas diagnosed on the basis of colour and smell of the blood. Aims and Objectives: To evaluate the efficacy of Babool and Kukundar and comparative clinical study of Babool and Kukundar on Asrigdara. Materials and Methods: For the present study, patients fulfilling the clinical criteria for diagnosis of Asrigdara will be selected irrespective of their age, sex, religion, etc, in random from O.P.D. section of M. M. M. Govt. Ayurveda College hospital, Udaipur (Raj.). Case history of all the patients was taken in the specially prepared proforma. Conclusion: Babool due to its astringent taste and Kunkundar due to its bitter taste, both drugs pacify excessive Pitta humour which is main cause of Asrigdara. Their chemical constituents possess haemostatic and anti-inflammatory properties thus considering these facts, these drugs have been selected for present study.